Facilitating matched pairing and expression of TCR chains introduced into human T cells - Kuball, Jürgen (American Society of Hematology, 2007)
Adoptive transfer of T lymphocytes is a promising treatment for a variety of malignancies but often not feasible due to difficulties generating T cells that are reactive with the targeted antigen from patients. To facilitate rapid generation of cells for therapy, T cells can be programmed with genes encoding the α and β chains of an antigen-specific T-cell receptor (TCR). However, such exogenous α and β chains can potentially assemble as pairs not only with each other but also with endogenous TCR α and β chains, thereby generating αβTCR pairs of unknown specificity as well as reducing the number of exogenous matched αβTCR pairs at the cell surface. We demonstrate that introducing cysteines into the constant region of the α and β chains can promote preferential pairing with each other, increase total surface expression of the introduced TCR chains, and reduce mismatching with endogenous TCR chains. This approach should improve both the efficacy and safety of ongoing efforts to use TCR transfer as a strategy to generate tumor-reactive T cells.